Mapeamento do campo elétrico de uma subestação usando a técnica dos elementos finitos - Martins, Alin do Amaral (2012)
In 2009 (may, 5) the law 11.934 was enacted, regulating the limits of human exposure to electric and magnetic fields originating from generation, transmission and distribution of electricity facilities. This law establishes that it is the responsibility of the electrical energy authority the measurement and adjustment of field values, if necessary. According to the rules the field to be measured should not be disturbed. In the case of the electric field, the object of the present study, this is impossible since the unit of measurement disturbs the field, even if the operator is located remotely. So, the aim of this work is to use an alternative method of estimating the electric field, based on the theory of finite elements, with application of the program FEMM, which simplifies the obtaining of the values and results in an undisturbed electric field.